Teilhard de Chardin’s Engagement with the Relationship between Science and Theology in Light of Discussions about Environmental Ethics - Galleni, Ludovico (Journal for the study of religion, nature and culture, 2005)
Pierre Teilhard de Chardin was among the most outstanding palaeontologists of the twentieth century. He was also a Jesuit whose task was to bring to the Church the novelty of the modern world. This novelty was evolution, the irreversible change in time characterized by a movement toward complexity and consciousness. Teilhard de Chardin proposed a research programme that would provide evidence for this increasing complexity in the animal evolution of canalizations and parallelisms. The most important of these was the move toward cerebralisation observed in various phyla. In order to investigate the mechanisms, he proposed biology as the science of the complexity of life, and geobiology as the science of the evolving biosphere. Teilhard de Chardin developed a synthesis with theology where humankind carried forward evolution with convergence towards the Omega point, the moment of the parousia of Christ. This eschatological perspective was strictly related to the survival of Earth, which itself allowed the emergence of humanity. At this point the preservation of the biosphere acquires all of its ethical value as it is the means to reach the eschatological task of the parousia of Christ. Finally, the relationship between the biosphere and the noosphere is suggested by the concept of symbiosis. In this way, the model of Teilhard de Chardin is a model of continuing exchange between science and theology with a reciprocal enrichment providing, among the many aspects, a new vision of the relationships between humankind and the biosphere.